PEMANFAATAN BAKTERI ANTAGONIS SEBAGAI AGEN BIOKONTROL PENYAKIT LAYU (Fusarium oxysporum f.sp. cubense) PADA TANAMAN PISANG - Susanna Susanna (Jurnal Floratek, 2006)
The Use of Antagonistic Bacterial as Biocontrol Agents to Wilt Disease (Fusarium oxysporum f.sp.cubense) on Banana Susanna Jurusan Hama dan Penyakit Tumbuhan Fakultas Pertanian Universitas Syiah Kuala Banda Aceh ABSTRACT             Fusarium wilt or panama disease caused by Fusarium oxysporum f.sp. cubense is on of the important disease on banana. Recently there is no such effective methode for controlling the disease. The use of fungicide to control the disease can make new races of the fungal pathogen is very virulent.  The use of biocontrol agent such as Pseudomonas fluorescens and Bacillus subtilis is alternative methode to control fusarium wilt.  The aim of this experiment was to find out the most effective antagonist bacterial to control fusarium wilt on banana.  The study was carried out in Mycology Laboratory of IPB and green house and Phytopathology Laboratory of Balitbio, Bogor from January to October 2001.  Six treatments in this experiment were arranged in randomized complete design with 3 replications.  The result showed that Pseudomonas fluorescens and Bacillus subtilis were reducing Panama disease fusarium wilt on banana. Both antagonistic bacterials were effective to control fusarium wilt.